1986
DOI: 10.1113/jphysiol.1986.sp016345
|View full text |Cite
|
Sign up to set email alerts
|

A gamma‐aminobutyric‐acid‐mediated baroreceptor input to supraoptic vasopressin neurones in the rat.

Abstract: SUMMARY1. Extracellular recordings in pentobarbitone anaesthetized male Long-Evans rats examined the influence of electrical stimulation in the diagonal band of Broca on the excitability of 113 putative vasopressin-secreting and 22 putative oxytocinsecreting neurosecretory neurones in the hypothalamic supraoptic nucleus.2. Single pulse or repetitive (5-20 Hz) stimulation in the ventral part of the diagonal band evoked a prominent reduction in the excitability of83 % ofvasopressinsecreting neurones with no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 34 publications
(37 reference statements)
1
46
0
1
Order By: Relevance
“…33 GABAergic afferents to AVP neurons mediate the reflexive inhibition of these cells by arterial baroreceptors. 15 In control rats (n=3), we found that the activation of baroreceptors by an intravenous injection of the α-adrenergic agonist phenylephrine (3-9 μg/kg body weight) resulted mostly in the inhibition of SON neurons (11 of 14 neurons; Figure 6A-6C, left panels). In contrast, in the DOCA-salt-treated rats (n=4), baroreceptor activation by phenylephrine mostly excited SON neurons (12 of 16 neurons; Figure 6A-6C, right panels).…”
Section: Depolarized E Gaba Converts Baroreflexive Inhibition Into Exmentioning
confidence: 97%
See 2 more Smart Citations
“…33 GABAergic afferents to AVP neurons mediate the reflexive inhibition of these cells by arterial baroreceptors. 15 In control rats (n=3), we found that the activation of baroreceptors by an intravenous injection of the α-adrenergic agonist phenylephrine (3-9 μg/kg body weight) resulted mostly in the inhibition of SON neurons (11 of 14 neurons; Figure 6A-6C, left panels). In contrast, in the DOCA-salt-treated rats (n=4), baroreceptor activation by phenylephrine mostly excited SON neurons (12 of 16 neurons; Figure 6A-6C, right panels).…”
Section: Depolarized E Gaba Converts Baroreflexive Inhibition Into Exmentioning
confidence: 97%
“…They also respond to pressure increases by inhibiting the vasoconstrictive center of the medulla and suppressing the electric activity of AVP neurons through the release of GABA. 15 The resulting decreases in heart rate, cardiac contractility, and AVP release from the posterior pituitary, along with vasodilation, cause blood pressure to decrease. Using the systemic administration of phenylephrine to interrogate the baroreflex, we discovered that arterial baroreceptor activation led to the excitation, rather than inhibition, of SON neurons in DOCA-salt model rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter pathway, activated by volume load, relays arterial baroreceptor information to the VP neurons in the SON and includes the diagonal band of Broca (DBB) that projects to and activates GABAergic neurons in the PNZ. In turn, PNZ neurons release GABA into the SON, inhibiting VPergic neurons, and thereby inhibit VP release after blood volume expansion (21,22,31,49). Recent studies have shown that volume expansion increases c-Fos positive cells in the PNZ and DBB (20 -22, 30).…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, electrophysiological studies have demonstrated that brief increases in blood pressure sufficient to activate peripheral baroreceptors evoke a selective GABAA receptor-mediated postsynaptic inhibition of VP neurones in SON (Jhamandas & Renaud, 1987). Diagonal band of Broca neurones participate in a central pathway transducing this depressant effect (Jhamandas & Renaud, 1986;Cunningham et al 1992). Anatomical evidence suggesting that they do not influence SON cells directly but act through GABAergic interneurones located in a SON perinuclear zone (Jhamandas et al 1989) have been recently supported by the observation that lateral hypothalamic lesions by ibotenic acid alter baroreceptor-evoked inhibition of SON-VP neurones (Nissen et al 1993).…”
Section: MD Brown School Of Sport and Exercise Sciences University Omentioning
confidence: 99%